Evaluation of hematological parameters in oral cancer and oral pre-cancer - Singh, Shruti; Singh, Jaya; Samadi, Fahad Mansoor; Chandra, Shaleen; Ganguly, Roop; Suhail, Shaista (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Oral squamous cell carcinoma (OSCC) is the most common public health issue in Indian population. Quite a large number of OSCC cases are preceded by potentially malignant disorders of oral cavity. The need for simple diagnostic marker for early diagnosis and thus better therapeutic outcome is imperative. The current study aims to evaluate hematological parameters such as hemoglobin, bleeding time, clotting time, total leucocyte count (TLC) and differential leucocyte count (DLC) in OSCC and oral potentially malignant disorder cases along with normal healthy controls. Methods: A total of 150 subjects; 50 in each group were taken and 2.5 ml of blood were withdrawn from each subject and TLC, DLC and hemoglobin assessment was done using autoanalyzer while bleeding time and clotting time was recorded through Duke’s method and modified Dale’s method respectively. Results: All the data were tabulated and recorded as mean±standard deviation and comparison was done using one-way ANOVA test (p<0.05). TLC count, neutrophil count and lymphocyte count showed statistically significant difference amongst three groups while other parameters such as hemoglobin percentage, bleeding time, clotting time, eosinophil count, monocyte count and basophil count were statistically non-significant. Conclusions: This study showed TLC count, neutrophil count and lymphocyte count might prove as useful determinant factor in oral squamous cell carcinoma and oral potentially malignant disorders. However, further study with larger sample size is required to establish their role as diagnostic, prognostic marker or predictor of malignant transformation.